2002
DOI: 10.1023/a:1019509803992
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These data demonstrate that ICDs provide safe and effective therapy in young patients. The indications for ICDs as primary preventive therapy remain uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…During the last two decades, ICD therapy has played an increasing role in the management of a diverse population of cardiac patients, such as ischemic and nonischemic cardiomyopathies and inherited proarrhythmic syndromes [4, 11]. Although ICD implantations in children are only 1% of those in adults, outcome data of ICD therapy in children are comparable with adult clinical trial data [2, 28, 29]. However, complication rate, incidence of infection, and frequency of inappropriate ICD shocks appear to be greater in children [6, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades, ICD therapy has played an increasing role in the management of a diverse population of cardiac patients, such as ischemic and nonischemic cardiomyopathies and inherited proarrhythmic syndromes [4, 11]. Although ICD implantations in children are only 1% of those in adults, outcome data of ICD therapy in children are comparable with adult clinical trial data [2, 28, 29]. However, complication rate, incidence of infection, and frequency of inappropriate ICD shocks appear to be greater in children [6, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The longer defibrillation coil of the subcutaneous lead compared with the shorter electrodes of the transvenous lead is more prone to accidents because of the high physical activity of patients. Although it has been thought that subcutaneous lead and abdominally-inserted active can is sufficient to establish a sufficient electrical field for defibrillation in the small chest of children, the mean defibrillation threshold at implant was higher (15.5 J) despite using various types of defibrillator implantation configurations compared with transvenous systems (11.5 J) (9, 15). A small displacement of the subcutaneous array may lead to an increase in the defibrillation threshold and failure of appropriate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were mostly female (12 patients; 80%), and the median age at implant was 14.9 months (IQR, 1.7-28.5). The majority received an ICD for secondary prevention (12 affecting a majority of the study group (8 patients; 53%). Three patients received an ICD for primary prevention (20%).…”
Section: Patient Characteristics and Indicationsmentioning
confidence: 99%
“…Multiple studies, however, have demonstrated the challenges associated with ICD use in children, including increased rates of inappropriate shocks, system malfunction, need for epicardial placement, and complications in younger patients. [7][8][9][10][11][12][13][14][15][16][17] The issues hampering ICD performance in children are even more pronounced in the smallest of pediatric patients: infants and toddlers (age, 0-3 years). This unique population has the added challenges of procedural complexity associated with device implantation, rapid growth in the first several years of life, markedly higher baseline and peak heart rates, and long-term ICD programming and management.…”
mentioning
confidence: 99%